2019
DOI: 10.33019/jstk.v1i1.1274
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic and Antioxidant Capacity of Acetone Extract of Tristaniopsis merguensis Leaves

Abstract: The purpose of this study was to determine the total phenolic and antioxidant capacity of Tristaniopsis merguensis leaf acetone extract. In this study extraction using the maceration method for 3 days with a ratio of dry leaves and solvents of 1: 10 (w / v). Analysis of total polyphenols in this study was carried out using the Follin-Ciocalteu method. Total polyphenols were measured based on gallic acid standards. The antioxidant capacity is calculated based on the DPPH method. The results of this study, obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The more phytochemical compounds that have antioxidant activity are extracted, the higher the antioxidant activity. Based on the results of the antioxidant activity test of the pelawan stem methanol extract, this is weaker when compared to the ethanol extract and acetone of pelawan leaves with consecutive IC 50 values of 18.2772 μg/mL (Enggiwanto et al, 2018) and 22.1454 μg/mL (Roanisca et al, 2019). It is due to the presence of alkaloids in pelawan leaves, while in pelawan stems, no alkaloids were found.…”
Section: Antioxidant Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…The more phytochemical compounds that have antioxidant activity are extracted, the higher the antioxidant activity. Based on the results of the antioxidant activity test of the pelawan stem methanol extract, this is weaker when compared to the ethanol extract and acetone of pelawan leaves with consecutive IC 50 values of 18.2772 μg/mL (Enggiwanto et al, 2018) and 22.1454 μg/mL (Roanisca et al, 2019). It is due to the presence of alkaloids in pelawan leaves, while in pelawan stems, no alkaloids were found.…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…Pelawan leaves contain secondary metabolites such as alkaloids, phenol, hydroquinones/tannins, and flavonoids. Another study found that the total phenolic content in pelawan leaves was 215.22 mg GAE/g dry extract and had a strong antioxidant activity with an IC 50 value of 22.1454 μg/mL (Roanisca, Mahardika, & Sari, 2019;Souhoka, Hattu, & Huliselan, 2019)). The research above shows that pelawan plants can be a source of antioxidants.…”
Section: Introductionmentioning
confidence: 98%
“…The sample of this research was kelubi fruit that comes from Nyelanding Village, Air Gegas District, South Bangka Regency. Furthermore, the flesh of the kelubi was taken and then it was blended and then squeezed using a clean cloth, centrifuged and filtered to got the kelubi fruit water which was clean from fruit solids (Roanisca ., 2019). Kelubi fruit water aws ready to be used as a catalyst (Patil, 2011).…”
Section: Preparation Of Natural Acid Catalyst Of Kelubi Fruit (Eleiod...mentioning
confidence: 99%
“…The Bangka Belitung Islands have various potential endemic plants to be developed [12]. One of the interesting plants to study is the 'Pucuk Idat' (Cratoxylum glaucum).…”
Section: Introductionmentioning
confidence: 99%